Hans Axel von Fersen i jego misja dyplomatyczna na dworze cesarskim w 1791 roku - Anusik, Zbigniew (Przegląd Nauk Historycznych, 2008)
Hans Axel von Fersen (born 1755) was a descendant of the rich and powerful Swedish aristocratic family. He was the eldest son of statesman count Fredrik Axel von Fersen. He was carefully educated at home and than he completed his education during the long journey abroad. In 1778 he entered the French military service with the Royal Baviere regiment. In the years 1780-1783 he took part in the American War of Independence. In 1783 he was made proprietary colonel of the regiment Royal Suedoise. Fersen was a very handsome and bold man. From the mid seventy's of 18th century he was an intimate friend and favourite of French Queen Marie Antoinette. When Gustav Ill's war with Russia broke out, in 1788, Fersen accompanied his monarch as an adjutant to Finland, but in the autumn of the same year was sent back to France. In January 1790 count Fersen became a special agent and correspondent of Gustav Ill. Before the end of the year he was forced to admit that the cause of the French monarchy was hopeless so long as the King and Queen of France were nothing but captives in their own capital. It was the reason why Fersen had the leading role in the Royal Family's "Flight to Varennes". From the beginnings of April 1791 the King of Sweden was informed about all conspirators' (one of them was Fersen) actions in Paris. Soon Gustav III resolved to take an important part in the restoration of ancien regime in France. On 17 May 1791 Swedish monarch described his plans in the letter addressed to the Louis XVI's most trusted emigree minister, Louis Auguste Le Tonnelier baron de Breteuil. Soon after sending that letter the sovereign of Sweden left Stockholm and went to Aix la Chapelle. There he waited for messages from count Fersen about successful escape of French Royal Family. Meanwhile, on 20 June 1791 Louis XVI and his family escaped from Tuilleries. But the next day the King was recognized and stopped at Varennes. When Gustav III obtained the message about unsuccessful "Flight to Varennes", he immediately defined his own aims in the policy against France. He excluded any negotiations with "the rebbels" and resolved that the most important thing in his future policy would be the full restoration of ancien regime in France. On 30 June 1791 Gustav III met in Aix la Chap elle Hans Axel von Fersen. During that meeting the King decided that Fersen should go to Vienna, where he should try to secure the Emperor's aid against the Revolution. On theSummer of 1791 the most important aim in Gustav Ill's policy was signing the alliance treaty with Russia. But the King did not neglect the necessity of gaining cooperation of other European courts. In the middle of July 1791 Gustav III sent his envoys to Vienna, London, Koblenz (the main seat of the French emigrees), Munch, Madrid and Kassel. The most important mission was the mission to Vienna because the German princes did not want to do anything without consent and cooperation of the Imperial Court. On the beginnings of August 1791 Hans Axel von Fersen came to Vienna. He tried to obtain two different aims. His King wanted him to convince the Imperial Court to the idea of open, armed intervention in the French internal affairs. But count Fersen, against the intention of his own monarch, gave the whole-hearted support to the idea of armed congress near borders of France, forced by the French Royal Couple and baron de Breteuil. Fersen desperately tried to induce the Emperor Leopold II and his ministers to accede a new coalition against revolutionary France or to support the idea of armed congress. But after a few weeks of insipid talks in Vienna and Prague count Fersen came to the conclusion that the Austrian court meant to do nothing at all. In October 1791, at his own request, count Fersen was transfered to Brussels, where he could be of more service to the Royal Couple of France. The assassination of the King of Sweden (16 March 1792) was a very painful blow for Hans Axel von Fersen and for all the followers of the French Royal Couple. The death of Gustav III (29 March 1792) meant retreat of Sweden from the participation in planned monarchical crusade against the French Revolution.